Rawls: constructivism and coherentist justification - Gondim, Elnora (Estudios de Filosofía, 2010)
Rawls has a Coherentist justification for justice as equity when he states that the Procedural Constructivism can be used to identify the Principles of the Justice of Citizens with various comprehensive morals doctrines making use of the Original Position, of Reflective Equilibrium and of a Public Reason.